PENGARUH ANGKUTAN DARING (DALAM JARINGAN) TERHADAP PEMINAT ANGKUTAN KOTA - Jopian, Perly; Elly Tri Pujiastutie; Endri Agustomi (JMTS: Jurnal Mitra Teknik Sipil, 2024)
Public transport is a much-needed means of transportation in many developing countries. The development of information and communication technology has greatly influenced the development of the transportation industry. Currently, there are internet-based transportation services or commonly called online  transportation. This has drawn opposition from several public transportation operators whose number of passengers has dropped since the introduction of online transportation. The purpose of this study is to determine the effect of online transportation on city transportation enthusiasts. This study was conducted by distributing questionnaires to the general public and interviewing people in several sub-districts of Bengkulu city. The method in this study is the analysis of pedestrialn preferences obtained by the stated preference technique with a rating scale. Chi-Square test to test the difference in proportion / percentage between several groups of data. And regression analysis is used to obtain the utility equation. Then the Stated Preference approach is a hypothesis to be assessed by respondents. The results showed that of the 96 respondents, 57 people or 59.375% chose online transportation, while 39 people or 40.625% chose city transportation. Of the several reasons for mode selection, in general, users of city transportation and online transportation choose, speed consideration factor of 23.96%, safety consideration factor of 17.71%, comfort consideration factor of 23.96%, ease of access factor of 18.75% and low price factor with a percentage of 11.46%. Abstrak Angkutan umum merupakan sarana transportasi yang sangat dibutuhkan di banyak negara berkembang. Perkembangan teknologi informasi dan komunikasi sangat mempengaruhi perkembangan industri transportasi. Saat ini sudah ada layanan transportasi berbasis internet atau biasa disebut transportasi daring (dalam jaringan). Hal ini menuai tentangan dari beberapa operator angkutan umum yang jumlah penumpangnya turun sejak diperkenalkannya angkutan daring (dalam jaringan). Tujuan dari penelitian ini adalah untuk mengetahui pengaruh angkutan daring (dalam jaringan) terhadap peminat angkutan kota. Kajian ini dilakukan dengan menyebarkan kuesioner kepada masyarakat luas dan mewawancarai masyarakat di beberapa kecamatan kota Bengkulu. Metode pada penelitian ini adalah analisa prerefensi pelaku pejalan di peroleh dengan teknik stated preference dengan skala rating. Uji Chi-Square untuk menguji perbedaan proporsi/presentase antara beberapa kelompok data. Dan analisa regresi digunakan untuk memperoleh persamaan utilitas. Dari hasil penelitian menujukkan bahwa dari 96 responden yang ada, sebanyak 57 orang atau 59,375% memilih angkutan daring (dalam jaringan), sedangkan sebanyak 39 orang atau 40,625% memilih angkutan kota. Dari beberapa alasan pemilihan moda, pada umum nya pengguna angkutan kota dan angkutan daring (dalam jaringan) memilih, faktor pertimbangan kecepatan sebesalr 23,96% faktor pertimbangan keselamatan 17,71% faktor pertimbangan kenyamanan 23,96% faktor kemudahan mengakses 18,75% dan faktor harga murah dengan persentase sebesar 11,46 %.